2021
DOI: 10.1007/s11136-021-02865-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of COVID-19 critically ill survivors after ICU discharge: 90 days follow-up

Abstract: Purpose The onset of the coronavirus disease 19 (COVID-19) pandemic in Italy induced a dramatic increase in the need for intensive care unit (ICU) beds for a large proportion of patients affected by COVID-19-related acute respiratory distress syndrome (ARDS). The aim of the present study was to describe the health-related quality of life (HRQoL) at 90 days after ICU discharge in a cohort of COVID-19 patients undergoing invasive mechanical ventilation and to compare it with an age and sex-matched s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 67 publications
6
59
1
1
Order By: Relevance
“…Missing data for the sexual activity dimension exceeded 20%, despite this aspect is in line with our previous follow-up [11] and data substitution was obtained with the multiple imputation technique, cautious interpretation of these data should be warranted.…”
Section: Limitationssupporting
confidence: 74%
See 4 more Smart Citations
“…Missing data for the sexual activity dimension exceeded 20%, despite this aspect is in line with our previous follow-up [11] and data substitution was obtained with the multiple imputation technique, cautious interpretation of these data should be warranted.…”
Section: Limitationssupporting
confidence: 74%
“…Several factors influenced the slope of HRQoL trajectories. In our previous study at 3 months after ICU discharge [11], we found that increasing age resulted negatively associated with HRQoL scores. Indeed, in the current follow-up, the "bad recovery" cluster showed a higher median age (Table 1).…”
Section: Health-related Quality Of Life Trajectoriesmentioning
confidence: 71%
See 3 more Smart Citations